System integration study of oxy-biosyngas combustion based metal heating process using Aspen Plus - Hu, Yukun; Chowdhury, Jahedul Islam; Katsaros, Giannis; Balta-Ozkan, Nazmiye; Varga, Liz; Li, Kang; Tassou, Savvas; Wang, Chunsheng (ICAE, 2020)
Given the increasing concerns on emissions, efficient and environmentally friendly combustion technologies are urgently needed to address energy trilemma. Metal heating is a large component of energy-intensive processes, as its energy consumption accounts for one third of the steel manufacturing process. Early attempts at using a new flameless oxy-fuel combustion burner give high performance, low NOx, and low-cost heating for the steel industry, while biosyngas is considered as an alternative fuel for reheating furnace with aiming at CO2 mitigation. Yet, all these technical solutions are developed in isolation. This paper investigates the system integration of biosyngas production, air separation unit (ASU), reheating furnace and heat recovery (HR) steam cycle, in order to enhance energy efficiency of steel industry and enable so-called negative emissions. An integrated system model was developed using Aspen Plus to evaluate the feasibility of the proposed integration from the perspective of heat and mass balance. In particular, to study the impacts of fuel switching on the heating quality of the furnace, a three-dimensional furnace model considering detailed heat transfer processes was embedded into the system. The simulation results show that the proposed system integration strategy is technically feasible. The electricity generation of the HR steam cycle used can compensate for about 90% of ASU’s energy consumption. The system is carbon capture-ready for being further integrated with CO2 conditioning and transportation processes
Keywords: Heat Recovery; Air Separation Unit; Oxy-fuel Combustion; Biosyngas Production; Metal Heating Process